WAYS TO INCREASE THE SERVICE TIME OF EXCAVATOR BUCKET TEETH - Zulfikorov Dostonbek Rustamjon oglu (Bright Mind Publishing, 2025)
Excavator bucket teeth at the present time 110G13L ( Gadfield steel i) is prepared from steel i. Broken in pieces this is a steel core of the resistance and the complexity viscosity eat has a unique combination of an institution. Its high elasticity (relative to stretched, beaten viscosity the cold, brittle limit) 1050°c at a temperature of birth obtained as a result of the features of stable manganese austenite core availability withstand eat - plastic deformation of steel during mechanical refinement ( naklyep ) is determined by a firm and strong core durability due to eat.
Keywords: Abrasive grinding , application solid coverage , manual arc mwf.